2014
DOI: 10.1038/cdd.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta signaling network regulates plasticity and lineage commitment of lung cancer cells

Abstract: Identification of target cells in lung tumorigenesis and characterization of the signals that control their behavior is an important step toward improving early cancer diagnosis and predicting tumor behavior. We identified a population of cells in the adult lung that bear the EpCAM þ CD104 þ CD49f þ CD44 þ CD24loSCA1 þ phenotype and can be clonally expanded in culture, consistent with the properties of early progenitor cells. We show that these cells, rather than being restricted to one tumor type, can give ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…We further revealed a positive correlation between TGFBR2 expression and prognosis of patients with human lung SCC. Although Tgfbr2 depletion could promote squamous lineage commitment in isolated lung epithelial precursor cells that harbor Kras G12D and p53 double mutants, genetic deletion of Tgfbr2 combined with other mutants in several mouse models significantly promotes lung ADC development, with absent or scarce SCC, challenging its in vivo role in determining squamous cell fate (18)(19)(20)(21). In this study, SCCs driven by Tgfbr2 loss exhibited the characteristic histopathology and biomarker expression of human SCC, manifesting the in vivo function of Tgfbr2 on suppressing SCC formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further revealed a positive correlation between TGFBR2 expression and prognosis of patients with human lung SCC. Although Tgfbr2 depletion could promote squamous lineage commitment in isolated lung epithelial precursor cells that harbor Kras G12D and p53 double mutants, genetic deletion of Tgfbr2 combined with other mutants in several mouse models significantly promotes lung ADC development, with absent or scarce SCC, challenging its in vivo role in determining squamous cell fate (18)(19)(20)(21). In this study, SCCs driven by Tgfbr2 loss exhibited the characteristic histopathology and biomarker expression of human SCC, manifesting the in vivo function of Tgfbr2 on suppressing SCC formation.…”
Section: Discussionmentioning
confidence: 99%
“…Sox2 is a well-established crucial transcription factor for squamous lineage commitment (8,11,19,(22)(23)(24). We next investigated the effects of canonical TGFb signaling pathway as well as ERK1/2 on SOX2 expression in two human lung ADC cell lines H441 and H358 and two human lung SCC cell lines SK-MES-1 and H520.…”
Section: Erk1/2 Cooperates With Smad4 To Repress Sox2 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis revealed that SMAD2 binding sequences were enriched at differentially methylated regions ( Figure 5D), potentially implicating the TGF beta pathway in sensitivity to GSK2879552. TGFbeta signaling is important throughout development and has been implicated in regulation of lung cancer cell plasticity, linking this pathway to cellular differentiation (Ischenko et al, 2014). Specific modulation of TGF-beta signaling in SCLC cells can inhibit their growth (Nørgaard et al, 1994;Sumitomo et al, 2000).…”
Section: Predictive Biomarker Of Sensitivity To Lsd1 Inhibition In Sclcmentioning
confidence: 99%
“…Transforming growth factor-β (TGF-β) signaling provides important regulatory signals during the initial phase of normal development and regeneration 113,114 and exerts promoting effects in the initiation and progression of multiple cancer types including breast, 115 colon, 116 liver, 117 lung, 118 and ovary. 119 TGF-β ligands bind to a type II receptor, which constitutively recruits and phosphorylates a type I receptor.…”
Section: Transforming Growth Factor-β Signaling Pathwaymentioning
confidence: 99%